(untitled) (Orfeu, 2018)
This paper presents methods, procedures and epistemological assumptions of a research methodology called Grounded Theory, along with a study of how it was applied to a doctoral research in music. This methodology is widely used in Social Sciences in the United States and European countries; however, it is still an uncommon practice in Brazil, especially in music studies. The main goal is to highlight the methodology potentials and drawbacks when applied in the field, by presenting some input to researchers who are interested in investigating (and/or theorizing) how social processes are worked out in music research. Findings show that such methodology, when applied to this research context, can be effective both for data collection and analysis process, as well as to the implementation of a substantive theory in the music field.